Religious-Mystical Conceptions in the Philosophy Of Tasavuf (Issues of Humanity And Divinity) - Jumaniyozova Dilfuza Kamalovna (Genius Publishing Group, 2023)
In the analysis of Western and Eastern literature and researches, secular and divine factors that improve the personality were studied, but it was found that not enough attention was paid to the harmony of humanity and divinity. Therefore, it is vital to study the relevance of the harmony of humanity and divinity in the spiritual development of a person. This article is based on the fact that in Eastern philosophy, humanity and divinity come as dialectically interrelated co-substantial realities (the existence of two foundations, and they are not exactly realities, but are manifested in the existence of an object in the form of side-by-side existence).
Keywords: Mysticism; philosophy; religion